Pediatric Psoriatic Arthritis: A Population-Based Cohort Study of Risk Factors for Onset and Subsequent Risk of Inflammatory Comorbidities. Issue 4 (October 2018) - Brandon, Timothy G.; Manos, Cynthia K.; Xiao, Rui; Ogdie, Alexis; Weiss, Pamela F.
Background: Relatively little is known about the epidemiology of juvenile psoriatic arthritis (PsA), including clinical features associated with the development of arthritis among children with psoriasis and subsequent risk of inflammatory comorbidities. Objective: To identify the overall risk of arthritis among children with psoriasis and subsequent risk of inflammatory comorbidities. Methods: Using Clinformatics DataMart (OptumInsight) deidentified US administrative claims data from 2000 to 2013, we identified children aged 0 to 16 years with an incident diagnosis of psoriasis or PsA using International Classification of Diseases, Ninth Revision, Clinical Modification diagnostic, procedure, and pharmacy billing codes. Cox proportional hazard regression was performed to assess clinical features associated with development of arthritis in children with psoriasis. Incidence rate ratios were used to compare the relative frequency of comorbid diagnoses. Results: We identified 212 children with PsA, 4312 with psoriasis only, and 45 240 controls. Approximately 33% of children with PsA received a diagnostic code for psoriasis before arthritis. Median time to index code for arthritis after index code for psoriasis was 17.6 months (interquartile range: 4.1-38.1). Older age and uveitis were associated with a significantly increased risk of developing arthritis in children with psoriasis. Children with PsA had a significantly increased risk of uveitis, diabetes, and depressive disorder when compared to patients with psoriasis and inflammatory bowel disease, uveitis, diabetes, and depressive disorder when compared to controls. Conclusion: Most children with PsA developed arthritis first. Older age and uveitis were risk factors for arthritis among children with psoriasis. Psoriatic arthritis was associated with an increased risk of several clinically relevant inflammatory comorbidities.